2022
DOI: 10.1155/2022/9010514
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Novel Immune Checkpoint-Related Model in Clear Cell Renal Cell Carcinoma

Abstract: Background. With the highest mortality and metastasis rate, kidney renal clear cell carcinoma (KIRC) is one of the most common urological malignant tumors and not sensitive to chemotherapy and radiotherapy. Immunotherapy, which proves to be effective and a big progression, such as PD-1/PD-L1 inhibitors, is not sensitive to all KIRC patients. To predict prognosis and immunotherapy response, a novel immune checkpoint gene- (ICG-) related model is essential in clinics. Methods. From the public database-downloaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The high-risk subgroup presented a higher TIDE score, meaning a worse response to immunotherapy. These results may also implicate the connection of the risk score-and lowered HHLA2 expression-with immunosuppressive responses [77].…”
Section: Hhla2 In Renal Cancermentioning
confidence: 85%
See 1 more Smart Citation
“…The high-risk subgroup presented a higher TIDE score, meaning a worse response to immunotherapy. These results may also implicate the connection of the risk score-and lowered HHLA2 expression-with immunosuppressive responses [77].…”
Section: Hhla2 In Renal Cancermentioning
confidence: 85%
“…Several studies indicated unfavorable clinical outcomes associated with the overexpression of HHLA2. However, multiple reports have identified HHLA2 as a protective factor [19,33,35,36,77]. Altogether, the number of studies tackling the issue of the role and expression of HHLA2 in different types of malignancies is poor, which results in contradictory conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, KEGG pathway enrichment analyses was applied and the results suggested that USP8 was mainly enriched in immune and metabolic processes, including ErbB signaling pathway, Ubiquitin mediated proteolysis, EGFR tyrosine kinase inhibitor resistance as well as PD-L1 expression and PD-1 checkpoint pathway in cancer. Emerging studies demonstrated that these pathway were signi cantly related to the occurrence, prognosis, and metastasis of KIRC [46-48] and PD-L1 expression and PD-1 checkpoint pathway [49] may be a molecular target and potential therapeutic strategy for USP8 in KIRC. Several research reported the underlying crosstalk between ErbB signaling pathway, Ubiquitin mediated proteolysis, EGFR tyrosine kinase inhibitor resistance, etc.…”
Section: Discussionmentioning
confidence: 99%